Petrogenesis and tectonic implications of two‐stage Cretaceous bimodal volcanism in the coast of Zhejiang Province, South‐east China. (26th September 2021) - Yu, Minggang; Wang, Qian; Hong, Wentao; Zhao, Xilin; Chu, Pingli
Abstract : Shipu volcanic area is located at the east of the Jiangshan‐Shaoxing Fault zone, an important part of the Mesozoic volcanic belt in the coastal south‐east China, which provides an excellent opportunity to study the origin of rarely outcropped and coexisting bimodal volcanic rocks and bimodal dyke swarms. Two stages of bimodal volcanic rocks and dyke swarms yield zircon U–Pb ages of ca. 118–121 Ma and ca. 95–93 Ma, respectively. Both bimodal magmatic rocks show enrichment in LILEs and LREEs, but depletion in HFSEs. Basalts of the early‐stage bimodal volcanism have whole‐rock ( 87 Sr/ 86 Sr)i ratio of 0.71121, ε Nd (t) value of −8.0, and zircon ε Hf (t) values of −19.3 to −11.7, while the contemporaneous rhyolites show whole‐rock ( 87 Sr/ 86 Sr)i ratios of 0.71023 to 0.71106, ε Nd (t) values of −7.5 to −6.6 and zircon ε Hf (t) values of −15.3 to −7.6 with TDM C of 0.96–2.11 Ga. Basaltic dykes of the late‐stage bimodal volcanism have whole‐rock ( 87 Sr/ 86 Sr)i ratios of 0.70898 to 0.70908, ε Nd (t) values of −5.8 to −5.7 and zircon ε Hf (t) values of −10.5 to 2.9, while coexisting rhyolitic dykes display whole‐rock ( 87 Sr/ 86 Sr)i ratios of 0.69618 to 0.71172, ε Nd (t) values of −3.1 to −3.0 and zircon ε Hf (t) values of −9.2 to 11.9 with TDM C of 0.37–1.71 Ga. These features suggest that the early‐stage basalts could be derived from partial melting of an enriched lithospheric mantle metasomatized by slab‐derived fluids, and its corresponding felsic end‐member is the product of partial melting of Proterozoic middle‐lower crust due to underplating of basaltic magmas with minor addition of mantle materials. As for the late‐stage bimodal volcanism, the basaltic dykes are also derived from an enriched mantle similar to the early‐stage counterpart. However, the rhyolitic dykes mainly originated from partial melting of ancient lower crustal materials with abundant input from the depleted mantle. As a whole, two stages of bimodal magmatism in Shipu area provide direct constraints on regional tectonic transition from an extensional arc setting to a back‐arc setting. Abstract : Two stages of bimodal magmatism including bimodal volcanic rocks and bimodal dykes are developed in Shipu area with zircon U–Pb ages of 118–121 Ma and 95–93 Ma, respectively. The mantle source of basalts and basaltic dykes changed from fluid‐metasomatism to melt‐metasomatism, while rhyolites and rhyolitic dykes were derived from partial melting of Proterozoic continental crust with minor addition of mantle materials and ancient lower crustal materials with abundant input from depleted mantle, respectively. Two stages of bimodal magmatism record the tectonic transition from an extensional arc setting to back‐arc setting.